Sediment transport calculation in two dimensions using the Einstein´s procedure a case study: the Zaire river - Mejía Marcacuzco, Jesús Abel (1987)
Universidad Nacional Agraria La Molina. Facultad de Ingeniería Agrícola. Departamento Académico de Recursos Hídricos